Teaching Methods as Correlates of Information Brokerage Entrepreneurial Skills Acquisition of Library and Information Science Undergraduates - Hope Chinyere Ilorah Chikaodi; Victor N. Nwachukwu; Florence Amaka Nwofor (Journal of Vocational Education Studies, 2022)
This study examined teaching methods as correlates of information brokerage entrepreneurial skills acquisition of Library and Information Science undergraduates. The study adopted a descriptive and correlational survey designs. The population was 200 and 300 levels students of Library and Information Science of Michael Okpara University of Agriculture, Umudike. Simple random sampling approach was used to select 200 students. Instrument for data collection was a structured questionnaire. Data collected were analyzed using frequency counts, mean and Pearson’s Product Moment Correlation Coefficient (r). Results showed that lecture teaching method was highly employed for information brokerage entrepreneurial skills. Students acquired bibliography compilation skills to a very high extent. Positive moderate correlation exist between teaching methods and information brokerage entrepreneurial skills. The study recommended that the federal government and the university management should provide adequate teaching facilities in Library schools.